Testing of scale parameter of the exponential distribution with known coefficient of variation: Conditional approach - Handa, BR; Kambo, NS; Ravindran, CD (Marcel Dekker Inc, 2002)
Tests of hypothesis of the parameter of the reduced exponential distribution E(atheta,theta) has been studied from a conditional viewpoint, based on the conditionality principle of R. A. Fisher. It is shown that conditionally, optimal tests are possible though unconditionally no such test exists. Some desirable properties of the conditional test and large sample approximations to the upper percentile point of the conditional test statistic are also presented. The equivalence of two ancillaries for conditioning with respect to power criterion is shown.
Keywords: conditional inference; UMP conditional test; power function; ancillary statistics